Fixed Assets Recording System at PT. The Great Ocean Ocean - Madiha Putri Khairat Ritonga; Rahmat Daim Harahap (Penerbit Jurnal Indonesia, 2022)
This study aims to collect as well as study the data and information needed in compiling and completing an internship final project regarding the recording system of fixed assets at PT.Samudera Lautan Luas. The research carried out is in the form of descriptive, namely the research method describes the object being studied objectively. used is primary data where the data is obtained directly by researchers from related parties at PT.Samudera Lautan Luas. Fixed assets at PT.Samudera Lautan Luas are assets whose useful life decreases as seen from the time of use and uses a recording system with the line method straight..